2017
DOI: 10.36685/phi.v3i3.130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Implementation of a Referral System in the Community Health Center of Abeli, Kendari, Indonesia

Abstract: Background: The referral rate in Southeast Sulawesi in the first-level health facilities was still high, which reached 17% in 2016. Ideally, the maximum referral rate in the first-level facilities should be no more 5%.  Objective: This study aims to evaluate the implementation of the first-level referral system in terms of availability of health personnel, facilities and medicines, and understanding of health officers on the referral system at the Community Health Center of Abeli.Methods: In-depth interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Our findings are consistent with other previous studies reporting inadequate supply of medicines or drugs affecting referrals, 12 , 13 and the subsequent action of patients in an effort to acquire better health services, particularly in developing countries, by-passing the primary level of care to a higher level. 34 The lack of drugs at healthcare facilities might impair equitable distribution, patient health, and referrals pathways. 13 Our study also identified improper patient flow as a barrier to the establishment of a referral system.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with other previous studies reporting inadequate supply of medicines or drugs affecting referrals, 12 , 13 and the subsequent action of patients in an effort to acquire better health services, particularly in developing countries, by-passing the primary level of care to a higher level. 34 The lack of drugs at healthcare facilities might impair equitable distribution, patient health, and referrals pathways. 13 Our study also identified improper patient flow as a barrier to the establishment of a referral system.…”
Section: Discussionmentioning
confidence: 99%